2018
DOI: 10.1002/jor.23869
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparison of rat monosodium iodoacetate and medial meniscal tear models of osteoarthritic pain

Abstract: Osteoarthritis (OA) is a degenerative form of arthritis that can result in loss of joint function and chronic pain. The pathological pain state that develops with OA disease involves plastic changes in the peripheral and central nervous systems, however, the cellular mechanisms underlying OA are not fully understood. We characterized the medial meniscal tear (MMT) surgical model and the intra-articular injection of monosodium iodoacetate (MIA) chemical model of OA in rats. Both models produced histological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
(86 reference statements)
1
15
0
Order By: Relevance
“…Havelin et al showed that advanced OA pain is associated with central sensitization, and two aspects of central sensitization, spinal sensitization and descending facilitation, are observed in rats with persistent ongoing pain. Brederson et al stated that p38 and phosphorylated extracellular signal‐regulated kinase (pERK) were increased in the spinal cord, and that phosphorylated cAMP response element binding protein (pCREB) was enhanced in the prefrontal cortex in the MIA‐induced knee OA model. MIA‐induced knee OA is characterized by central sensitization and neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Havelin et al showed that advanced OA pain is associated with central sensitization, and two aspects of central sensitization, spinal sensitization and descending facilitation, are observed in rats with persistent ongoing pain. Brederson et al stated that p38 and phosphorylated extracellular signal‐regulated kinase (pERK) were increased in the spinal cord, and that phosphorylated cAMP response element binding protein (pCREB) was enhanced in the prefrontal cortex in the MIA‐induced knee OA model. MIA‐induced knee OA is characterized by central sensitization and neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the pain mechanism for hip OA, we have reported an animal model of monosodium iodoacetate (MIA)‐induced hip OA and evaluated the expression of calcitonin gene‐related peptide (CGRP) and activating transcription factor 3 (ATF3) in the dorsal‐root ganglia (DRG) and the expression of the ionized‐calcium‐binding adapter molecule 1 (Iba1) in the spinal cord . In MIA‐induced knee OA model in rats, some studies reported duloxetine attenuated the neuropathic pain . To the best of our knowledge, no report investigated the effect of duloxetine on neuropathic pain and its mechanism in hip OA animal model to date.…”
mentioning
confidence: 99%
“…Therefore, this model is not commonly used to study the progression of OA as the damage it causes does not mimic true OA as well as certain other models. Instead, it is mainly used to observe and evaluate pain behavior and to assess the efficacy of therapeutic interventions to reduce inflammation and pain [36][37][38][39].…”
Section: Chemically Induced Modelsmentioning
confidence: 99%
“…However, they do have utility for studying the mechanism by which OA causes pain and the behavioral changes resulting from this pain. Also, these models are useful for evaluating the efficacy of different drug therapies which can be used to alleviate the pain experienced by people afflicted with OA [32][33][34][35][36][37][38][39].…”
Section: Chemically Induced Modelsmentioning
confidence: 99%
See 1 more Smart Citation